Who Bore the Brunt of the Pandemic in Europe? : Shifting Private Stress to the Public Sector - Arena, Marco; Chen, Ruo.; Cuevas, Alfredo; Foda, Karim (Washington, D.C. : International Monetary Fund, 2021)
In Europe, the severe human toll of the COVID-19 pandemic was compounded by the deepest fall in economic activity in modern history. Yet this huge decline in output did surprisingly little damage to the aggregate financial balance sheets of firms and households. This paper discusses how unprecedented policy support transferred private sector income losses to the public sector's balance sheet and contrasts this experience to that of the global financial crisis.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet
Keywords: Business Fluctuations; Cycles; Macroeconomics; Saving; Wealth